Analisis Risiko Usaha Peternakan Ayam Broiler Dengan Pola Kemitraan Di Desa Sampean Kecamatan Sungai Kanan Kabupaten Labuhanbatu Selatan Provinsi Sumatera Utara - Rika Putri Harapan Tanjung; Sri Ramadhani; Nuri Aslami (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to analyze the risk of broiler chicken farming with a partnership pattern in Sampean Village, Sungai Kanan District, South Labuhanbatu regency, North Sumatra province. This study uses descriptive qualitative methods with data collection techniques, namely observation, interview, and documentation. The results showed that in the cultivation of broiler chickens is inseparable from the existence of business risks, the most common risks are production risks and price risks. Production risks faced by farmers in Sampean Village are the risk of dead chickens, stressed chickens, chickens exposed to disease, and price or market risks. The strategy in overcoming the risk is the identification of risks by tracing the risks contained in broiler chicken farming, evaluation / risk analysis by evaluating the risks after knowing what are the sources of risks faced by farmers such as the causes of chicken deaths, controlling risks by designing the best and economical way to reduce the risk of chicken deaths by providing drugs or vaccines provided by partner companies and herbal medicines formulated by farmers themselves. However, broiler chicken farmers in Sampean village have obstacles in overcoming their business risks, namely the lack of competence of farmers in overcoming the risks that exist in broiler chicken farming businesses.